2023
DOI: 10.3390/covid3050058
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of COVID-19 Vaccine Uptake and Hesitancy among Healthcare Workers in Tanzania: A Mixed-Methods Study

Abstract: The novel Coronavirus disease 2019 (COVID-19) presents a major threat to public health but can be prevented by safe and effective COVID-19 vaccines. Vaccine acceptance among healthcare workers (HCWs) is essential to promote uptake. This study, aimed to determine the COVID-19 vaccination uptake and hesitancy and its associated factors among HCWs in Tanzania. We employed a convergent-parallel mixed-methods design among 1368 HCWs across health facilities in seven geographical zones in Tanzania in 2021. We collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Subsequent studies reported HCWs’ acceptance towards the COVID-19 vaccines [ 43 , 57 , 65 , 68 , 74 , 75 , 78 , 86 , 87 , 89 , 90 , 93 , 95 ]. Among these ten studies, over half of the participants were vaccinated with at least one dose (see Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequent studies reported HCWs’ acceptance towards the COVID-19 vaccines [ 43 , 57 , 65 , 68 , 74 , 75 , 78 , 86 , 87 , 89 , 90 , 93 , 95 ]. Among these ten studies, over half of the participants were vaccinated with at least one dose (see Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The following factors associated with VA were gender [ 23 , 46 , 56 , 65 , 67 , 72 , 74 , 76 , 77 , 79 , 80 , 87 ], age [ 43 , 46 , 48 , 54 , 56 , 57 , 65 , 74 , 87 , 94 ], education level [ 43 , 46 , 50 , 52 , 67 , 75 , 78 ], belonging to religion [ 48 , 74 ], marital status [ 43 , 72 , 76 , 77 , 78 ], being a parent [ 95 ], absence of pregnancy [ 43 ], presence of chronic illness [ 43 , 56 , 59 , 77 ], living area [ 65 , 67 , 77 , 79 ], cadre [ 23 , 43 , 48 , 49 , 51 , 53 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations